A comunicação da ciência e a literatura no diário de pilar em Machu Picchu - Thaís Cabral Leocádio (2019)
The Communication of Science and Literature in the Diário de Pilar em Machu Picchu Can a book for children and young people be considered informative and literary at the same time? To what extent can these two classifications coexist - or not - coexist? Children and youth literature establishes itself as a vanguard place, open for experimentation. This study is based on the book Diário de Pilar em Machu Picchu, fourth volume of the series Diário de Pilar, written as journal by Flávia Lins e Silva, illustrated by Joana Penna and published by Zahar, in 2014. The study aimes to discuss the interrelationships between communication, science, literature and education, seeking to analyze the limits and tensions between literary fiction and science communication, both in verbal and non-verbal texts. The relevance of this research relates to the importance of science communication in children literature, considering the technological society we live in. In addition to combining different languages, the multimodal character of the object of study is a prominent element in the analysis, since the series protagonist is the author of a blog. The character Pilar emerges from the printed book and, existing on its own real life blog, corresponds directly to the readers who write her in the web. Academic reference is made to authors who discuss themes such as: science and society (BRONOWSKI, 1986; ROSSI, 2001, 2006); scientific divulgation (SÁNCHEZ-MORA, 2003); illustrated book (BELMIRO, 2012); information book (GARRALÓN, 2015); intermedia (CLÜVER, 2011; RAJEWSKY, 2012 and RIPPL, 2015); communication of science (LOPES, 2013); literature and character building (CANDIDO, 1976 and 2012), among others. Research tools included a bibliographical survey, interviews with the writer and analysis of the book - considering aspects of the discourse (literature and information) and the graphic design developed by Joana Penna. In the surveyed work, important aspects to information books were observed, such as the presence of a glossary and expository text, even so the presentation of those resources was only possible through the fictional narrative. The choice of writing the book as a traveling diary was an artifice that allowed different narratives, types and textual genres to coexist in the same work. The Diário de Pilar em Machu Picchu presents the potential for children and youth literature to make science communication without leaving the aesthetic out.